2020
DOI: 10.3390/ijerph17031026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acute Responses to Two Different Cycling Sprint Interval Exercise Protocols with Different Recovery Durations

Abstract: Background: Knowledge of acute responses to different sprint interval exercise (SIE) helps to implement new training programs. The aim of this study was to compare the acute physiological, metabolic and perceptual responses to two different SIE cycling protocols with different recovery durations. Methods: Twelve healthy, active male participants took part in this study and completed four testing sessions in the laboratory separated by a minimum of 72h. Two SIE protocols were applied in randomized order: SIE6×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Furthermore, it was demonstrated that the ability to repeat these high-intensity efforts was the difference between elite and non-elite male and female cyclists [ 7 , 22 , 23 ]. Therefore, it is very important to take into account the type of power meter for the registry and analysis of these efforts [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that the ability to repeat these high-intensity efforts was the difference between elite and non-elite male and female cyclists [ 7 , 22 , 23 ]. Therefore, it is very important to take into account the type of power meter for the registry and analysis of these efforts [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both SIE sessions were performed on a cycle ergometer (Ergomedic Monark 894, Vansbro, Sweden) in accordance with the protocol described by Danek et al [ 27 ] and presented in Figure 1 . Each session was preceded by a 10-min warm-up at 60% VO 2 max obtained in the incremental test; during the warm-up, two 5-s all-out accelerations were performed in the third and sixth minute.…”
Section: Methodsmentioning
confidence: 99%
“…Knowing the hormonal responses after performing a single exercise session can indicate the direction of selecting an appropriate training strategy, which is important because of the great interest in endocrine responses due to the use of training modulation determining the level of changes in testosterone or cortisol concentrations [ 2 ]. Previous multifaceted analyses of current responses in a single interval exercise (SIE) session have focused primarily on determining changes in cardiorespiratory parameters that determine physical performance [ 3 ]. As reported by Riachy et al [ 4 ], data on the effects of exercise on serum testosterone levels in men show considerable inter-individual and inter-study variability.…”
Section: Introductionmentioning
confidence: 99%